STRATEGI BAWASLU KABUPATEN LOMBOK UTARA DALAM MENCEGAH PELANGGARAN NETRALITAS APARATUR SIPIL NEGARA PADA PEMILIHAN KEPALA DAERAH TAHUN 2020 - MASDIYANTO MASDIYANTO; SANDI JUSTITIA PUTRA; ISMI ARIFIANA RAHMANDARI; DENDA DEVI SARAH MANDINI; ZULHADI ZULHADI; YANI ROSITA SARLAN (GANEC SWARA, 2024)
This study aims to determine the strategy of the North Lombok Regency General Election Supervisory Body in preventing violations of the neutrality of the State Civil Apparatus. Where in its prevention, the North Lombok Regency Bawaslu makes prevention efforts that have special attention to the State Civil Apparatus in the North Lombok Regency environment. This study was conducted on the strategy or prevention efforts carried out by the North Lombok Regency General Election Supervisory Body using data analysis then narrated, sourced from interview activities, observations, document excavations. The strategies used by the North Lombok Regency General Election Supervisory Body are in the form of Appeals, coordination, socialization, supervision villages and utilization of social media. That the North Lombok Regency General Election Supervisory Body has maximized prevention of violations of the neutrality of the State Civil Apparatus in North Lombok Regency. Potentials have been mapped and prevention strategies have been prepared in supervising the 2020 Regional Head Election in North Lombok Regency. This study found a strategy in preventing violations of the neutrality of the State Civil Apparatus based on hierarchical instructions and initiatives from the North Lombok Regency General Election Supervisory Body